POTENSI VEGETASI HUTAN KOTA DALAM REDUKSI EMISI KARBONDIOKSIDA (CO2) DI KOTA JAMBI - Handika, Rizki Andre; FITRADA, WATHRI; RODHIYAH, ZULI (Universitas Jambi, 2020)
Abstract, Urban Forest is one of the Public Green Open Space which is controlling atmosfer, water, and soil pollution. Carbon dioxide (CO2) is one of the emission substances of greenhouse gas sources. Increased concentration of CO2, which comes from burning fuel oil and gas, can cause various diseases, such as upper respiratory tract infections, heart disease, cancer and etc. Therefore, it is necessary to reduce CO2 emissions, which one of them is through the utilization of Public Green Open Space, especially urban forest. Jambi City as the most populous area in Jambi Province has high CO2 emission potential. The purpose of this research is to predict the potential of tree vegetation in urban forest in Jambi City in reducing CO2 gas. The research was conducted in 3 locations: Bagan Pete Urban Forest, Muhammad Sabki Urban Forest, and Pine Forest Kenali. The vegetation analysis was performed using the Quadrant Method, where the 10 x 10 m observation plot was determined randomly. Vegetation analysis at each location was conducted to obtain basal area, which then determined the potential of CO2 emission reduction. The basal area of the trees vegetation at each location was 72,72 m2/Ha, 25,45 m2/Ha and 5,12 m2/Ha. Reduction of CO2 of tree vegetation in urban forest in each location in sequence was 41386 Ton/Ha/Year, 14482.93 Ton/Ha/Year, 2916.94 Tons/Ha/Year. Bagan Pete Urban Forest has the highest reduction potential. Based on this research, total carbon dioxide emission reduction potential through urban forest in Jambi City was 58785,87 Ton/Ha/Year.